SEXIST LANGUAGE USED IN “THE JAKARTA POST” - Wulandari, Sri Wahyuni; Purwaningsih, Endang; Hawasi, Hawasi (Journal of Language and Literature, 2016)
This research report has discussed about "sexist language" The sexist language refers to words or vocabularies that identified the markers of sexist language uses in the media such as “The Jakarta Post”. The basic problems were the usage of sexist language and classify it into three markers, they were non-parallel, lexical asymmetry and generic pronoun/word and also that terms were related to the feminist stylistic in linguistic theory. Actually the sexist language that found was indicated to the jobs title and occupation. Sexist language was mostly dominated by male, it can be seen from the data that found. This research purposed to find out the markers of sexist language and the relation between sexist language uses with feminist. The data has collected from newspaper that was “The Jakarta Post”. From 120 data the writer found that 2 data non-parallel structure, 21 data lexical asymmetry, and 97 data generic Pronoun and word. So it can be concluded that male gender was dominant from the data.Keywords: sexist, sexist language, markers of sexist language, feminist